The Role of the Court in Providing Legal Certainty for the Return of the Name of the Land Certificate When the Seller Is Unknown - Zaini, Zulfi Diane; Harliansyah, Ari (Faculty of Law, Universitas Pattimura, 2026)
Introduction: This study analyzes the juridical aspects of the renaming of land title certificates when the seller's whereabouts are unknown, referring to Decision Number 8/Pdt.G/2024/PN.Gdt. The practice of buying and selling land that is not immediately registered causes a mismatch between physical control and juridical data, hampering the process of changing the name. Purposes of the Research: This research aims to identify the factors that cause these obstacles as well as the basis for the judge's consideration in validating the land sale and purchase certificate. Methods of the Research: Using normative and empirical juridical methods with qualitatively analyzed secondary data and interviews. Results Main Findings of the Research: It was found that the main causes included delays in the registration of transfer of rights, long physical possession of land, the absence of sellers, and limited administrative authority of the National Land Agency. The judge certified the sale and purchase certificate based on the fulfillment of the legal conditions of the agreement, strong evidence, the good faith of the plaintiff, and for the sake of legal certainty and order of land administration.